Clinical utiliy of a model‐based piperacillin dose in neonates with early‐onset sepsis. Issue 3 (30th September 2021) - Wu, Yue‐E; Hou, Shan‐Shan; Fang, Zeng‐Yu; Tang, Bo‐Hao; Yao, Bu‐Fan; Dong, Yi‐Ning; Li, Xue; Shi, Hai‐Yan; Zheng, Yi; Hao, Guo‐Xiang; Huang, Xin; Van Den Anker, John; et al.
Abstract : Aims: Early‐onset sepsis (EOS) is a common disease in neonates with a high morbidity and mortality rate. Piperacillin/tazobactam has been used extensively and empirically for EOS treatment without clinically validated dosing regimens, although the population pharmacokinetics (PPK) of piperacillin in neonates has been reported. Therefore, we wanted to study the effectiveness and tolerance of a PPK model‐based dosing regimen of piperacillin/tazobactam in EOS patients. Methods: A prospective, single‐centre, phase II clinical study of piperacillin/tazobactam in neonates with EOS was conducted. The dosing regimen (90 mg·kg −1, q8h) was determined based on a previous piperacillin PPK model in young infants using NONMEM v7.4. The pharmacodynamics (PD) target (70%fT > MIC, free drug concentration above MIC during 70% of the dosing interval) attainment was calculated using NONMEM combined with an opportunistic sampling design. The clinical treatment data were collected. Results: A total of 52 neonates were screened and 49 neonates completed their piperacillin/tazobactam treatment course and were included in this analysis. The median (range) values of postmenstrual age were 33.57 (range 26.14–41.29) weeks. Forty‐seven (96%) neonates reached their PD target. Eight (16%) neonates experienced treatment failure clinically. The mean (SD, range) duration of treatment and length of hospitalization were 100.1 (62.2, 36.2–305.8) hours and 31 (30, 5–123) days. There were no obvious adverse events and no infection‐related deaths occurred in the first month of life. Conclusions: A model‐based dosing regimen of piperacillin/tazobactam was evaluated clinically, was tolerated well and was determined to be effective for EOS treatment.